Prospects for the Implementation of HIV Molecular Transmission Network–Informed AIDS Prevention and Control in China. Issue 3 (30th September 2022) - Feng, Yi; Xing, Hui; Ruan, Yuhua; Liao, Lingjie; Shao, Yiming
Abstract: The human immunodeficiency virus (HIV)–infected population with a transmission link has a strong genetic similarity in viral gene sequences that tend to cluster. In recent years, a strategy for guiding HIV/acquired immunodeficiency syndrome (AIDS) prevention using sequence-based transmission networks has been proposed. The execution of this strategy provides an opportunity to effectively control the spread of the AIDS epidemic in China. HIV molecular transmission network research has been actively pursued by a number of Chinese research groups. Medium- and long-term strategies were created with the goal of using HIV molecular transmission networks to guide targeted prevention and control in China. Technical guidelines for HIV transmission network monitoring and intervention have been written and released. Pilot studies are continuing in the meantime. Despite the fact that this strategy has a bright future, there are still many challenges to overcome to achieve the intended AIDS prevention and control goals.